Proposal (39) to conserve the name Koelerietalia splendentis Horvatić 1973 as a nomen conservandum - Dengler, Jürgen; Vassilev, Kiril; Bergmeier, Erwin (Vegetation Classification and Survey, 2024)
After a nomenclatural revision of the available names for the order of rocky grasslands of the Balkan Peninsula within the class Festuco-Brometea , based on Article 52 ICPN we propose the conservation of the name Koelerietalia splendentis against the name Halacsyetalia sendtneri . In syntaxonomic concepts not combining the limestone and serpentine rocky grasslands of the Balkans in a single order, the latter name would still be available as it is based on a different nomenclatural type. (39) Koelerietalia splendentis Horvatić 1973 nom. cons. propos. Typus: Chrysopogono grylli-Koelerion splendentis Horvatić 1973 (holotypus) (=) Halacsyetalia sendtneri Ritter-Studnička 1970 Typus: Potentillion visianii Ritter-Studnička 1970 (lectotypus: Kuzmanović et al. 2016) Taxonomic reference : Mucina et al. (2016). Abbreviations : ICPN = International Code of Phytosociological Nomenclature, 4 th edition (Theurillat et al. 2021).